Detection of RAPD markers linked to resistance to cassava anthracnose disease - Akinbo, Olalekan; Gedil, Melaku A; Ekpo, E.J.A.; Oladele, J.; Dixon, Alfred G.O. (2007)
Cassava anthracnose disease (CAD) is a major stem disease of cassava (Manihot esculenta Crantz) in the cassava growing areas of the world. To identify markers associated with resistance to CAD, F1 progenies were produced from a cross between resistant genotype TME 117, and susceptible genotype TMS 920326, as the experimental population. The chi-square test gave a goodness of fit for the expected ratio of 1:1 for resistant to susceptible genotypes suggesting a monogenic dominant inheritance. Two hundred decamer primers were screened using both resistance and susceptible parent to CAD. Bulk segregant analysis was quickly used to search for Random amplified polymorphic DNA (RAPDs) linked to anthracnose resistance in F1 derived from TMS 920326 and TME 117. The fragment linked to the gene was flanked on both sides by primers OPAF2 and OPF06 at 13.1 and 22.2cM. To our knowledge this is the first report on this fungal disease of cassava and of molecular markers that is tag CAD resistance in cassava. We discuss the use of markers-linked to CAD1 for marker-assisted cassava breeding.